1985
DOI: 10.1017/s0141347300011058
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Responsiveness in Behavioural Marital Therapy

Abstract: There is empirical evidence demonstrating the effectiveness of behavioural marital therapy. However the issues of predicting outcome and the responsiveness of particular marital problems to behavioural treatments, while crucial, have been largely ignored. Forty-five couples requesting therapy were consecutively assigned to either conjoint treatment, couples group treatment or treatment of one partner alone to ascertain whether a screening profile could be developed that would predict treatment outcome. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…We briefly review the previous research with respect to these classes of predictors. 1 Regarding demographic variables, four studies have found evidence of more favorable treatment outcome for younger couples (Baucom & Aiken, 1984;Bennun, 1985;Hahlweg, Schindler, Revenstorf, & Brangelmann, 1984;O'Leary & Turkewitz, 1981), but three other studies failed to replicate these findings (Crowe, 1978;Jacobson, Follette, & Pagel, 1986;Mendonca, Lumley, & Hunt, 1982). Two studies have revealed conflicting relationships between education and success in treatment, and one study found that less educated couples responded more favorably (Crowe, 1978); however, another study found no relationship between education and treatment success (Mendonca et al, 1982).…”
mentioning
confidence: 99%
“…We briefly review the previous research with respect to these classes of predictors. 1 Regarding demographic variables, four studies have found evidence of more favorable treatment outcome for younger couples (Baucom & Aiken, 1984;Bennun, 1985;Hahlweg, Schindler, Revenstorf, & Brangelmann, 1984;O'Leary & Turkewitz, 1981), but three other studies failed to replicate these findings (Crowe, 1978;Jacobson, Follette, & Pagel, 1986;Mendonca, Lumley, & Hunt, 1982). Two studies have revealed conflicting relationships between education and success in treatment, and one study found that less educated couples responded more favorably (Crowe, 1978); however, another study found no relationship between education and treatment success (Mendonca et al, 1982).…”
mentioning
confidence: 99%
“…Atkins et al [12] points out that couples that experience infidelity tend to experience approximately the same distress following treatment than couples who present with no fidelity related issues. Fidelity issues appear to be one of the most difficult relationship problems to treat and jealousy possibly impossible to treat [13][14][15]. In addition, only approximately 50% of the couples receiving therapy for infidelity appear to demonstrate significant progress by the end of therapy [16].…”
Section: Sexual Addiction Rehab-dr Drew Saves the World Of Cheaters!mentioning
confidence: 99%
“…Fifteen therapists were asked to identify (1) areas which they believed to be important in marital harmony and (2) the areas they would assess during initial interviews. Information from clients was obtained in the context of a marital therapy study (Bennun, 1985) where 57 couples were specifically requested to identify their targets for change. Targets reported included the request that their partner alter specific behaviours or habits that were felt to be irritating or unpleasant ( 19% :I.…”
Section: Test Specijicationmentioning
confidence: 99%